Transmigran sebagai Modal Sosial dalam Pengembangan Food Estate di Kabupaten Pulang Pisau - Evi Fitriana; Marni Marni (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2021)
Agriculture is a sector that plays an important role in supporting sustainable development. Transmigration since the time of the Dutch East Indies has been synonymous with the food program. One of the objectives to be achieved from the transmigration program is to improve the welfare of transmigrant farmers. This research is a qualitative descriptive study which aims to describe and analyze the social capital owned by transmigrants for the development of the food estate program in Pulang Pisau Regency. This research focuses on: 1) networks, 2) trust, and 3) social norms. The Food Estate development program has a link between social capital. Social capital is the main factor that transmigrants must have to support the Food Estate program. Social capital indicators that need to be considered in developing Food Estate are: a) Network, farmers need a network to develop agriculture (Ministry of Environment, Ministry of Agriculture and Minister of National Defense). Social networks between agricultural actors are also potential social capital to support the Food Estate program; b) Trust, the Food Estate development program has received support from the central government to the community, so this indicates that there is trust from the government and society in increasing national food security while simultaneously improving the welfare of agricultural actors; c) Social Norms, in developing the Food Estate program, a legal basis is needed related to agriculture.